Peruvian Shamanism in the West and Coping with Bulimia: A Case Study - Lentine, Melissa (Religious studies and theology, 2012)
Spirituality and religion are acknowledged as playing a vital role in psychological coping within monotheistic (especially Christian) and American populations. Other traditions, however, remain largely absent from the coping literature. In addition, the bulk of the work consists of quantitative methods, so the examination of the constructs remains limited. In the present study, a 49-year old Caucasian woman living in northern Indiana in the U.S. is interviewed about her use of shamanistic beliefs and rituals to cope with bulimia. Content analyses reveal that over the course of the interview, she identifies shamanic rituals as facilitating a change from feeling powerless to feeling empowered to alter the bulimic behaviors. Related themes concerning energy and strength also emerge and stand in relation to an expression of the importance of an internalized system of beliefs. These observations align with the predominately monotheistic American literature, suggesting that principles of religious and spiritual coping may be meaningful in the context of other traditions.